Effectiveness of the Gladdy Moddy intervention in enhancing parental readiness and maternal-fetal attachment - Maulina, Rufidah; Novika, Revi Gama Hatta; Sari, Atriany Nilam; Maulida, Luluk Fajria; Nurhidayati, Siti; Wahidah, Nurul Jannatul (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to assess the impact of Gladdy Moddy (Glad Mom and Daddy), an intervention comprising education, a gratitude journal, and a support group, on maternal-fetal attachment and parental readiness. Methods: This research was conducted from June to July 2024 in the villages of Trengguli and Sidomukti, under the jurisdiction of the Jenawi Health Center in Karanganyar. A pre-experimental design with a one-group pre-test and post-test was employed. A total of 23 couples were recruited using purposive sampling. Results: Initial scores for mother-fetus bonding, measured using the Prenatal Attachment Inventory (PAI), were 59.2, while scores for parental readiness, measured by the Maturity to Parenthood Scale (MPS), were 140.7. Post-test results indicated a significant increase, with PAI scores rising to 64.5 and MPS scores to 149.4. Bivariate analysis using a paired t-test revealed significance levels of 0.028 (p < 0.05) for PAI and 0.020 (p < 0.05) for MPS. Conclusion: The Gladdy Moddy intervention had a significant positive impact on prenatal attachment and parental readiness among mothers. This approach can be effectively used to prepare couples for parenthood and enhance the bond between mother and fetus.